Altorientalische Altertümer in Museen und Privatsammlungen - Weidner, E.
London: 182-183 — Oxford (1949; 1950; 1951; 1952; 1953): 183-185 — Birmingham: 185 — Istanbul: 188 — Baghdad: 188-189 — Cambridge: 191 — St. Louis: 191 — Worcester (Persepolis): 192.